Interpretation of tongues and prophecy in 1 Corinthians 12-14 : with a Pentecostal hermeneutics - Ahn, Yongnan Jeon (Journal of Pentecostal theology. Supplement series ;, 2013)
Bringing "spiritual experience" into the domain of biblical hermeneutics, this book will certainly stimulate current debates within this field, among both Pentecostals and Christians of other traditions. The author also applies a Pentecostal hermeneutical methodology to Paul's teaching on tongues and prophecy in 1 Corinthians 12-14, opening possibilities to a Pentecostal pneumatology that tends instead to focus on the Lukan narrative. Paul's texts are reconsidered not as doctrinal or situational documents but as dynamic communication within a living community.